أبعاد الأفعال الكلامية في الشعر الثوري قصيدة نشيد الرجال لــ محمود درويش - صالحي, قصبة, معمر محمد الصالح (Univercty of Eloued, 2020)
تناكؿ ىذا البحث دارسة تداكلية في نظرية الفعؿ الكلبمي بكصفو كؿ ممفكظ يقكـ عمى شكؿ إنجازم يحمؿ معنى كدلالة كتأثير كىك في ظاىره المادم عبارة عف نشاط تركيبي نحكم يحمؿ أفعالا لتحقيؽ غايات كأغارض إنجازيو قكلية كالأمر كالنيي كالكعد. ..كأىداؼ تأثيرية حيف تنعكس عمى المتمقي فيبدم رفضا أك قبكلا حيث يكمف الجانب التأثيرم لمفعؿ(يمس المتمقي) مف الناحية الاجتماعية أك كؿ ما يتصؿ بو كىنا يكمف الإنجاز لمفعؿ . فقاـ البحث عمى تناكؿ ىذه المفاىيـ بالتفصيؿ مدعما الدارسة النظرية في الفصؿ الأكؿ بدارسة تطبيقية في الفصؿ الثاني ضمف مدكنة شعرية لمشاعر الثائر محمكد دركيش بعنكاف (نشيد الرجاؿ) أيف كقفنا عند أىـ أبعاد الأفعاؿ الكلبمية مف خلبؿ تصنيفاتيا كتقسيماتيا مركزيف عمى القكة الإنجازية ككذا متضمنات القكؿ، محاكليف قدر اؿمستطاع إبارز الدلالات، كالمقاصد . ؼ قادتنا جكلتنا التحميمية في عكالـ قصيدة نشيد الرجاؿ إلى أبعاد كفضاءات غير متناىية تكتظ دلالة، كتزدحـ صكار، كتعج أفعالا، حركت ما تكارل بيف ممفكظاتيا، ؼشكمت الأفعاؿ الكلبمية منطمقيا الفعمي بأغمب تصنيفاتيا بدءا بالإعلبنيات مركار إلى الإخباريات استدارة إلى التكجيييات كقكفا عند الكعديات انتياء بالتكجيييات، فكانت سمسمة كلبمية ممفكظية ارتبطت حمقاتيا مف بداية القصيد إلى نيايتو. This research deals with a deliberative study in the theory of verbal action as every utterance is based on a constructive form that carries meaning, significance and influence, and in its material form it is a syntactic and syntactic activity that carries actions to achieve verbal goals and objectives such as the command, prohibition and promise ... and influential goals when reflected on the recipient and expresses rejection Or acceptance where the effectual aspect of the verb (touching the recipient) resides from the social point of view or everything related to it and here lies the achievement of the action. So the research deals with these concepts in detail, supporting the theoretical study in the first chapter with an applied study in the second chapter within a poetic blog of the revolutionary poet Mahmoud Darwish entitled (The Anthem of Men or nachid errijell) Where did we stand at the most important dimensions of verbal actions through their classifications and divisions, focusing on the achievement power as well as the implications of the saying, Trying as much as possible to highlight the indications,‌and the purposes. Our analytical tour in the worlds of the "nachid errijell" poem led us to infinite dimensions and spaces crowded with significance, crowded with images, and teeming with actions, moving what was hidden among their pronouncements. Verbal verbs formed their actual starting point in most of their classifications, starting with advertisements, passing through to informative, turning to directives, standing at promises and ending with directives, so it was a verbal verbal chain whose episodes were linked from the beginning of the poem to the end.
Keywords: الأفعال الكلامية - الشعر الثوري